Byzanz in Europa: Europas östliches Erbe ; Akten des Kolloquiums "Byzanz in Europa" vom 11. bis 15. Dezember 2007 in Greifswald - Altripp, Michael (Byzantios, 2011)
The role of Byzantium in the Middle Ages is comparable to that of a modern political superpower such as the United States. The latter has a pervasive cultural impact on Europe and Asia, and similar cross-cultural relationships between East and West were also evident in medieval Europe, when Byzantine literature, music, art, and ritual were not only known but also studied and appropriated throughout the West. Scholarship on Byzantium and its relationship with Western Europe has yet to explore the full dynamics of this relationship or the extent to which the West was influenced by Byzantine culture. The papers presented in this volume offer a wide interdisciplinary perspective on the crucial importance of Byzantium for Western Europe, featuring articles on art and architectural history, social and religious history, musicology, literature, historiography, gender studies. The essays originate from an interdisciplinary conference, held in the Wissenschaftskolleg Greifswald in December 2007